Enhancing TB treatment adherence through the application of the Behaviour Change Wheel - Hulisani Matakanye; Takalani Grace Tshitangano (Taylor & Francis Group, 2024)
Non-adherence to tuberculosis (TB) treatment poses a significant challenge, leading to multidrug-resistant TB and extensively drug-resistant TB. Addressing TB treatment non-adherence is crucial for curing individual patients, controlling TB spread, and reducing TB drug resistance. This study aimed to enhance TB treatment adherence through the application of the Behaviour Change Wheel. The BCW guide was followed to develop the intervention strategy for improving TB treatment adherence among patients. The process involved eight steps across three stages: understanding the behavior, identifying intervention options, and determining content and implementation options. Stage 1 data comprised 16 interviews with TB patients, three with TB district managers, eight with facility operation managers, eight with facility TB focal persons, and three focus group discussions with 18 direct observed treatment supporters. Findings from Stage 1 informed the intervention strategy development. A one-day stakeholder workshop, guided by Stages 2 and 3 of the BCW model, was conducted. The COM-B model analyzed results to identify necessary changes. The BCTv1 taxonomy helped select appropriate behavior change strategies for the intervention. The intervention strategy, named Adherence Improvement Management Strategy (AIMS), was developed through the stakeholder workshop, integrating insights from both approaches and guided by the last two stages of BCW. AIMS involves door-to-door campaigns by community health workers, distributing patient information leaflets to patients, communities, and family members. The BCW framework proved valuable in developing an intervention strategy to enhance TB treatment adherence among patients. Recent research indicates that AIMS is well-structured, patient-centered, coordinated, accessible, safe, and of high quality.